The Influence Of Perceived Organizational Support And Organizational Citizenship Behavior (OCB) On Job Satisfaction With Motivation As An Intervening Variable At The It Rabbani Sutera Foundation - Wahyudi, Zikri (Journal of Science Education and Management Business, 2024)
Therefore, organizational management needs to pay special attention to the development of OCB as a strategy to enhance Motivation and ultimately increase Job Satisfaction at the Rabbani Sutera IT Foundation. Rabbani SDIT and SMPIT Alam School is an Integrated Islamic school that combines Islamic values (Character) with intellectual abilities, building students' character through exemplary behavior by teachers and the environment, making nature the primary medium in achieving learning objectives. The aim of this research is to determine and analyze the Influence of Perceived Organizational Support and Organizational Citizenship Behavior (OCB) on Job Satisfaction with Motivation as an Intervening Variable. The research method used is quantitative research, with a sample size of 39 respondents. This study uses SEM analysis using SmartPLS 3 and data collection techniques through questionnaire distribution using Likert scales. Based on the results of the study exploring the influence of Perceived Organizational Support, Organizational Citizenship Behavior (OCB), and Motivation on Job Satisfaction at the Rabbani Sutera IT Foundation. The most dominant result of the study indicates that Organizational Citizenship Behavior (OCB) has a significant influence on Motivation, suggesting that enhancing OCB can be a relevant strategy to improve employee motivation in the organizational environment. Additionally, Motivation has a positive and significant influence on Job Satisfaction. The implication is that efforts to enhance Motivation in the organizational environment can improve employee Job Satisfaction